Development of Laser Scanner for Full Cross-Sectional Deformation Monitoring of Underground Gateroads - Yang, Qianlong (2018)
The deformation of underground gateroads tends to be asymmetric and complex. Traditional instrumentation fails to accurately and conveniently monitor the full cross-sectional deformation of underground gateroads. Here, a full cross-sectional laser scanner was developed, together with a visualization software package. The developed system used a polar coordinate measuring method and the full cross-sectional measurement was shown by 360° rotation of a laser sensor driven by an electrical motor. Later on, the potential impact of gateroad wall flatness, roughness, and geometrical profile, as well as coal dust environment on the performance of the developed laser scanner will be evaluated. The study shows that high-level flatness is favorable in the application of the developed full cross-sectional deformation monitoring system. For a smooth surface of gateroad, the sensor cannot receive reflected light when the incidence angle of laser beam is large, causing data loss. Conversely, the roughness surface shows its nature as the diffuse reflection light can be received by the sensor. With regards to coal dust in the measurement environment, fine particles of floating coal dust in the air can lead to the loss of measurement data to some extent, due to scattering of the laser beam.